Good Leaders Ask Great Questions: Resep Kepemimpinan Inspiratif: Indonesia - Rizal Mahendra; Nurizzati (Literaksi: Jurnal Manajemen Pendidikan, 2023)
The purpose of this study is to present a review of the book Good leaders ask great questions: foundations for successful leadership by John C. Maxwell. Descriptive qualitative method used in this study, the source of the material obtained by analyzing the contents of the book. The results of this review speak volumes about a practical guide for leaders looking to improve their leadership skills. Full of questions that can stimulate the people around them to think, innovate, and grow.